Zina Menurut Pandangan Al Qur’an (Kajian Tafsir Tematik Tentang Ayat-Ayat Zina) - Achmad . (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2018)
Adultery is to have intercourse between men and women without a legitimate marriage bond. Al-Qur'an talks about adultery in three letters, namely: first, al-Qur'an, al-Isra verse (32). Secondly, al-Qur'an al-Nur verse (2) and verse (3). Third, Al-Furqan verse 68. The first verse (QS. Al-Isra 'verse 32) contains a prohibition on approaching adultery. The second (QS.An-nur verse 2-3) contains the law for the perpetrators of adultery and the prohibition of marrying it, and the third verse QS. Al-Furqan verse (68) contains the reply of the perpetrators of adultery later in the sight of Allah. In Islam the word zina includes zina muhshan and ghairu muhshan. Limitation of adultery which must be had is 12 (twelve), namely: 1) Mukallaf, 2) male, 3) including all the hasyafah (penis tip), 4) original sex, 5) the genitals are still integrated with the person, 6) inserting clear sex in women, 7) law is prohibited to include it is indeed in the dzatiyah, 8) the law of prohibition arises from reality, 9) there must be no syubhat aborted on had, 10) the sex must be interested in character, 11) perpetrator zina must fulfill Islamic laws, and 12) the perpetrator must understand the prohibition of adultery.